EMPLOYEE SATISFACTION ANALYSIS (Case study on Employee Contract PT. Kharisma Ide Nusantara Garmindo Cibitung - Bekasi) - Sabila Nurul Imanda; Apriatni Endang Prihatini; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2012)
Human resources are the most important resource in a company. Therefore, the management of the company should be able to manage its human resources properly in order to achieve job satisfaction for employees. The research was carried out at PT. Kharisma Ide Nusantara Garmindo Cibitung – Bekasi which object was contract employees. Based on the list of employees absent and late, as well as production data known that there is an enhancement of contract employee’s absent and late, as well as the enchancement of reject goods from 2010 to 2011. This research aims to determine the level of contract employee satisfaction at PT. Kharisma Ide Nusantara Garmindo Cibitung – Bekasi which showed from compensation, control, the work itself, labor relations, and job guarantees.  Type of research is explanatory research. The data used in this study is primary data obtained using a questionnaire data collection instrument. The population in this study were all contract employees of PT. Kharisma Ide Nusantara Garmindo and 84 respondents as the sample that used purposive sampling technique. Analysis of the data used in this research is a method of Importance – Performance analysis. Based on the Importance - Performance analysis concluded that the average of total variable compensation is equal to 85.45%, which is included in the category of very satisfied, for control variable is equal to 79.10% is included in the category are satisfied, for the variable itself is the work of 75.91% is included in the category are satisfied, for the variables of employment is equal to 79.64% is included in the category are satisfied, for the variables of job security is at 75.13% is included in the category are satisfied. It means that respondents are generally satisfied with the performance of compensation, control, the work itself, labor relation, and job guarantees at PT. Kharisma Ide Nusantara Garmindo Cibitung - Bekasi. But there were respondents that have less satisfied with the opportunities to leave in company, the monitoring system by using the tools, employee transportation facilities, adequate working equipment, as well as retirement. Advice can be given to companies is to improve the performance of companies that are considered important by the employees, but still received less attention from the company.